Analysis of TATA-box binding protein associated factor 4b gene mutations in a Chinese population with nonobstructive azoospermia - Xi, Qi (Medicine (Baltimore), 2020)
Nonobstructive azoospermia (NOA) is a severe form of male infertility. The molecular basis of NOA is still poorly understood. The aim of this study was to explore the associations between single nucleotide polymorphisms (SNPs) of the TATA-box binding protein associated factor 4b (TAF4B) gene and NOA. A total of 100 Han Chinese patients with NOA and 100 healthy men as controls were recruited. Targeted gene capture sequencing was performed. A total of 11 TAF4B SNPs were screened in the NOA and control subjects. Six synonymous and 4 nonsynonymous variants were detected. The c.11G>T (p.G4V) mutation was detected only in NOA patients. Polymorphism Phenotyping v2 and Sorting Intolerant From Tolerant analysis indicated that the p.G4V mutation influenced the protein structure of TAF4B. Haplotype analysis showed that the candidate SNPs did not independently associate with NOA and were found at extremely low frequencies in the subject population. Mutation Taster analysis indicated that the c.11G>T/p.G4V mutation was damaging. WebLogo analysis showed that the residue at amino acid 4 was relatively conserved. The p.Gly4Val substitution may affect the structure of the TAF4B protein. The c.11G>T mutation of the TAF4B gene may be associated with NOA in a Chinese population. Bioinformatics analysis indicated this variation may play an important role in the process of spermatogenesis.